Reputations, Relationships, and Contract Enforcement - MacLeod, W. Bentley (Journal of Economic Literature, 2007)
When the quality of a good is at the discretion of the seller, how can buyers assure that the seller provides the mutually efficient level of quality? Contracts that provide a bonus to the seller if the quality is acceptable or impose a penalty on the seller if quality is unacceptable can, in theory, provide efficient incentives. But how are such contracts enforced? While the courts can be used, doing so involves high real costs. Informal enforcement, involving a loss of reputation and future access to the market for any party that defaults on a contract, may often be a better alternative. This paper explores the use of both formal and informal enforcement mechanisms, provides a rationale for a variety of observed market mechanisms, and then generates a number of testable hypotheses.